Psychometric properties of the Chinese version of the Dispositional Greed Scale and a portrait of greedy people. (15th January 2019) - Liu, Zhenzhen; Sun, Xiaomin; Ding, Xuechen; Hu, Xinyan; Xu, Zhengqi; Fu, Ze
Abstract: Greed is ubiquitous in human existence. However, empirical research on greed is surprisingly rare, in part due to a lack of sound scales to measure it. This article reports on 3 studies that test the Chinese version of the Dispositional Greed Scale (DGSC) using 4 samples with a total of 1048 participants. Study 1 and study 2 provide evidence for the factorial validity, internal consistency, convergent validity and criterion-related validity of the DGSC. Study 2 and study 3 present evidence for the concurrent validity of the DGSC from three aspects: a) the DGSC was positively correlated with Belief in a Zero-Sum Game and subjective socio-economic insecurity; b) the DGSC was negatively correlated with all facets of core self-evaluations (i.e., self-esteem, generalized self-efficacy, locus of control, neuroticism) except neuroticism, with which the DGSC was positively correlated; and c) the DGSC was negatively correlated with all facets of external core evaluations (i.e., trust in people, belief in a just world, belief in a benevolent world). These findings provide new insight into the nomological net of greed and shed light on the beliefs and behaviors of greedy people in economic transactions and their fundamental attitudes toward the self, others and the external environment.